International Energy R&D Spillovers and the Economics of Greenhouse Gas Atmospheric Stabilization - Valentina Bosetti; Carlo Carraro; Emanuele Massetti; Massimo Tavoni (Fondazione Eni Enrico Mattei (FEEM), 2007)
It is widely recognized that technological change has the potential to reduce GHG emissions without compromising economic growth; hence, any better understanding of the process of technological innovation is likely to increase our knowledge of mitigation possibilities and costs. This paper explores how international knowledge flows affect the dynamics of the domestic R&D sector and the main economic and environmental variables. The analysis is performed using WITCH, a dynamic regional model of the world economy, in which energy technical change is endogenous. The focus is on disembodied energy R&D international spillovers. The knowledge pool from which regions draw foreign ideas differs between High Income and Low Income countries. Absorption capacity is also endogenous in the model. The basic questions are as follows. Do knowledge spillovers enhance energy technological innovation in different regions of the world? Does the speed of innovation increase? Or do free-riding incentives prevail and international spillovers crowd out domestic R&D efforts? What is the role of domestic absorption capacity and of policies designed to enhance it? Do greenhouse gas stabilization costs drop in the presence of international technological spillovers? The new specification of the WITCH model presented in this paper enables us to answer these questions. Our analysis shows that international knowledge spillovers tend to increase free-riding incentives and decrease the investments in energy R&D. The strongest cuts in energy R&D investments are recorded among High Income countries, where international knowledge flows crowd out domestic R&D efforts. The overall domestic pool of knowledge, and thus total net GHG stabilization costs, remain largely unaffected. International spillovers, however, are also an important policy channel. We therefore analyze the implication of a policy mix in which climate policy is combined with a technology policy designed to enhance absorption capacity in developing countries. Significant positive impacts on the costs of stabilising GHG concentrations are singled out. Finally, a sensitivity analysis shows that High Income countries are more responsive than Low Income countries to changes in the parameters and thus suggests to focus additional empirical research efforts on the former.
Keywords: H0; H2; H3; 330; Climate Policy; Energy R&D; International R&D Spillovers; Stabilization; Klimaschutz; Forschung; Spillover-Effekt; Energieforschung; Technischer Fortschritt; Welt